Расчет мощности потерь и температуры структуры транзисторно-диодных модулей при компьютерном моделировании преобразователей - Жемеров, Г.Г.; Ивахно, В.В.; Ковальчук, О.И. (Електротехніка і електромеханіка, 2011)
A calculation method for the total instant power of static and dynamic losses and transistor-diode modules transition temperature is considered under discrete simulation of semiconductor converters by means of MatLab (Simulink) in modes with a quantization interval in models close to the transistor turn-on and turn-off times.